2007
DOI: 10.1021/ie070089i
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of the Oxidative Dehydrogenation of Ethane in an Electrochemical Packed-Bed Membrane Reactor

Abstract: The feasibility of the oxidative dehydrogenation of ethane to ethylene with alumina-supported vanadium oxide catalyst (VO x /γ-Al2O3) in an electrochemical packed-bed membrane reactor was investigated at temperatures between 500 and 620 °C with molar ratios of oxygen to ethane of 0.06−3.10. An oxygen-ion-conducting yttria-stabilized zirconia (YSZ) membrane was employed in a reactor of Au|YSZ|Pt, and the oxygen flux transferred across the membrane was controlled over the faradic coupling of oxygen-ion conductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…The model, including the equations for charge transfer reactions of oxygen on the cathode and the anode ( 7.12 -7.14 ), was not able to predict the experimental results of the EMR operation conditions with electrochemically supplied oxygen. One reason for the discrepancies between the experimental data and the simulated was concuded to be the additional electrochemically induced side reactions, as suggested already by Chalakov et al ( 2007 ), Ye et al ( 2004 ) and Ye et al ( 2005 ). In contrary to the co -feed mode, where the oxygen on the anode exists only in form of gaseous O 2 , additional oxygen species, e.g.,…”
Section: Analysis Of Oxidative Dehydrogenation Of Ethane In a Solid Ementioning
confidence: 91%
See 4 more Smart Citations
“…The model, including the equations for charge transfer reactions of oxygen on the cathode and the anode ( 7.12 -7.14 ), was not able to predict the experimental results of the EMR operation conditions with electrochemically supplied oxygen. One reason for the discrepancies between the experimental data and the simulated was concuded to be the additional electrochemically induced side reactions, as suggested already by Chalakov et al ( 2007 ), Ye et al ( 2004 ) and Ye et al ( 2005 ). In contrary to the co -feed mode, where the oxygen on the anode exists only in form of gaseous O 2 , additional oxygen species, e.g.,…”
Section: Analysis Of Oxidative Dehydrogenation Of Ethane In a Solid Ementioning
confidence: 91%
“…In the experimental investigation of ODHE was found that the ethylene selectivity was not positively infl uenced in the solid electrolyte membrane reactor operation compared to the packed -bed membrane reactor operation (Chalakov et al , 2007 ). The selectivity ratio S S CO CO 2 was found to depend on the type of oxygen supply, so that with a gaseous oxygen supply the ratio was always lower than that with an electrochemically supplied oxygen.…”
Section: Analysis Of Oxidative Dehydrogenation Of Ethane In a Solid Ementioning
confidence: 95%
See 3 more Smart Citations